Pilon fractures: a review of current classifications and management of complex Pilon fractures. Issue 2 (April 2017) - Sivaloganathan, Sivan; Pedersen, Jens Brahe; Trompeter, Alex; Sabri, Omar
Abstract: Pilon fractures result mainly from high energy injuries. Owing to this, the implications on the long-term prognosis are significantly affected by the damage inflicted during the event. Improving the prognosis will inevitably involve a multidisciplinary approach, taking into consideration a number of variables. Reducing the overall risk of complications through soft tissue protection whilst implementing appropriate treatment objectives through well timed surgery will aid the clinical outcome. In this article we review Pilon fractures, their aetiology, current classifications, and their management.